Attitudes and Opinions of Adolescent Females Regarding 2 Methods of Bladder Filling for Transabdominal Ultrasound: A Q-Sort Study. Issue 8 (August 2020) - Waterhouse, Marie R.; Pham, Phung K.; Chang, Todd P.
Abstract : Objectives: Adolescent female patients who are not sexually active and who present to a pediatric emergency department with abdominal pain require a full bladder prior to transabdominal ultrasound. Procedures to fill the bladder are largely institution or provider dependent. We examined adolescent females' attitudes and opinions toward 2 common methods of bladder filling, intravenous fluid administration and transurethral Foley catheter placement, by means of a Q-sort study. Methods: Two convenience samples of adolescent female patients in the pediatric emergency department at an academic children's hospital participated in the study. In part 1, subjects underwent a semistructured interview to elicit their opinions regarding 2 methods of bladder filling: intravenous fluid or transurethral catheter. The summation of subject statements was then narrowed down to a final Q set of 25 statements. In part 2, a second sample of subjects independently arranged this Q set according to their own agreement or disagreement with each statement. Principal components analysis was conducted to examine factors or collections of statements representing a shared viewpoint and to describe commonalities. Results: Part 1 was completed with 9 subjects, and part 2 with 26 subjects. Factors revealed from the Q-sort data included acceptance of tests deemed medically necessary, desire for parental involvement, and a wish to minimize discomfort. Most adolescents aligned with 1 of these 3 factors. Conclusions: Adolescent female patients varied in their attitudes and opinions regarding intravenous catheter hydration and Foley catheter placement for transabdominal ultrasound. Knowledge of adolescent viewpoints may help better inform practitioner-patient communication for this procedure. Abstract : Supplemental digital content is available in the text.